Celah Hukum Spionase: Cukup dengan Hukum Kebiasaan atau Tata Cara Perang Perlu Pembaharuan? - Yosia, Edson Septo; Pebrianto, Dony Yusra; Farisi, Mochammad (Faculty of Law, Universitas Jambi, 2021)
At first, war was only carried out by the disputing parties but as the times progressed, the war also had an impact on the surrounding area or other countries. Arrangements for war need to be made such as war treaties or procedures. One of the unclear regulations concerning the act of espionage or what is known as spying. International humanitarian law regulates the customs of war and the manner of war. It turns out that the convention does not clearly regulate the legal protection of spy agencies. This article tries to discuss the urgency of protecting spy agents who are serving in war under humanitarian law.